"El sistema de costos y su incidencia en la productividad de la purificadora de agua prodiayal S.A. en el año 2012" - Changoluisa Gavilanes, Diana Patricia (2014)
This project was based on the basis of a comprehensive evaluation conducted during the month of July 2012, performed according to the information gathered in Prodiayal S. Water Purifier A. The research was based on the descriptive method, not experimental, because it’s based on achieving objectives. In developing research sought to establish whether Prodiayal S. A. Water Purifier, had a cost system that would provide the necessary tools for the development of a production cost, as a basis for making management decisions. It also sought, through field research, identify the consequences that the way they are currently determining the unit cost of product that the company currently processes, such as bottle jugs of purified water type. All research requires a logical and orderly process of data collection, clear information flow at the right time, to obtain reliable results, for this reason were taken based on the following points: Preliminary information to identify the activities that are taking place throughout the production process of the company; Observation and data collection through questionnaires and interviews; Observation entire production phase.